STUDENT PERCEPTIONS ON TEACHING SKILLS OF STUDENTS PRACTICAL TEACHING AND LEARNING PROGRAMME IN SOCIAL STUDIES LEARNING - Lili Dianah; Tetep (Institut Pendidikan Indonesia, 2022)
This study aims to analyze students' perceptions toward PLP (Scool Introduction) students teaching skills in social studies learning. This study uses a descriptive quantitative approach. The research sample consisted of 224 respondents from 7 state junior high schools in Garut Regency. The sample that became the object of research was grade 8 students. The samples were drawn using stratified random sampling. The results showed that PLP students in the class, according to students' perceptions: 1) The teaching skills ability in social studies learning was medium category; 2) Attainment The highest indicator of teaching skills was the students ability to open lessons, including: conveying learning objectives, conveying the benefits of the material to be studied as a form of motivation, and conducting apperception, namely associating the material that has been studied with the material that will be studied; 3) The lowest ability was the ability to utilize learning resources and media, including when teaching less use of learning media such as pictures or videos and only using textbooks, not using other learning resources.